An analysis of students' preparation for the virtual learning environment - Lee, Joseph; Ng, Lai Hong; Ng, Lai Ling (Elsevier, 2001)
While improving quality, reducing costs, and increasing access are the key issues being discussed by administrators and academics of higher education, the advances in the information and communication technologies (ICT) have been perceived as the solution to problems relating to these issues. The literature on the uses of ICT in higher education has provided much information describing the design and development of a technical framework for supporting the virtual learning environment (e.g., Kostopoulos [Internet Res.: Electron. Networking Appl. Policy 8 (1998) 257.]; Jafari [WebNet J. (1999).]; Chia et al. [Paper presented at the International Conference on the Emerging Trends in Electronic Commerce 2000, Kuala Lumpur (2000).]). Many studies have examined the designs of online courses (e.g., Human & Kilbourne [J. Manage. Educ. 23 (1999).]; St. Pierre [WebNet J. (1999, July–September).]; Chuang [Interact. Multimedia Electron. J. Comput.-Enhanced Learn. 1 (1999).]; Thompson & McGrath [J. Asynchronous Learn. Networks 3 (1999).]; Leon & Parr [Am. Stat. 54 (2000).]; Kaynama & Keesling [J. Mark. Educ. 22 (2000).]). Some studies have compared students' learning experiences in online courses (e.g., Hiltz et al. [J. Asynchronous Learn. Networks 4 (2000).]; Wegner et al. [J. Asynchronous Learn. Networks 3 (1999).]; Ernest & Federico [J. Asynchronous Learn. Networks 4 (2000).]; Fallah & Ubell [ALN Mag. 4 (2000).]; Watters [J. Educ. Bus. 75 (2000).]). The processes of collaboration and communication between learners and teachers are increasingly computer-mediated, such as via the Internet. From the learner's perspective, perhaps the most significant and detrimental factors to the success of a virtual learning environment are stress, association with technology use, and dissatisfaction towards the technology itself. It is suggested, conceivably, that the success of any virtual learning environment depends on the adequate skills and attitudes of learners. This proposition is evidenced by the popularity of online course delivery at postgraduate level when compared with undergraduate degree courses; as it is commonly believed that postgraduate students are mature and motivated to undertake self-study as required in most virtual learning environments. The authors present a study with the purpose to access preparation of learners. A questionnaire, comprised of adoptions of several existing instruments (Teo & Lim [Women Manage. Rev. 11 (1996).]; Stone & Arunachalam [Issues Account. Educ. 11 (1996).]; Chau [J. Manage. Inf. Syst. 13 (1996).]; Compeau & Higgings [MIS Q. 23 (1999).]; McMahon et al. [J. Comput. Assisted Learn. 15 (1999).]; Shaw & Peter [J. Asynchronous Learn. Networks 4 (2000).]; Venkatesh & Morris [MIS Q. 24 (2000).]), was administered to appraise experiences with computers and attitudes toward computers of students enrolled in a private college offering tertiary education in Malaysia. Awareness of information available on the Internet, access to the Internet, age, perceived effectiveness, and usefulness of ICT in study are suggested to be important factors in determining learners' use of the Internet in a virtual learning environment. The aim of this study is to identify factors that address the requirements of learners to enable appropriate use of ICT in their learning.